Study of Bacterial Resistance against Antibiotics in Patients Body Fluid Germs - S Farahmand Rahimabadi; L Kenarsari Moqadam; S Alizadeh (Tehran University of Medical Sciences, 2007)
Background: Increase of bacterial resistance against antibiotics makes some difficulties in patient's treatment and it is essential to study of antibiotics situation and bacterial sensitivity pattern against antibiotics. Physicians often get soon start to treatment patients based on bacterial quantities and bacterial sensitivity against antibiotics that seem always is not an effective treatment and make to spread some resistant species against antibiotics and increase their quantities in populations. So determination of antibiotic sensitivity in bacterium get from patients is important to an effective treatment. Methods: various body fluids include of cerebrospinal fluid synovial fluid pleural and ascite fluid get from patients were studied during one year. All samples were cultured to probably growth of bacterium by standard method in Qazvin Avicenna hospital. gram positive and gram negative bactries were separated. Bacterial sensitivity test were done by NCCLS standard method and get some importable results that show us we couldn't guess bacterial resistance pattern against antibiotics. Results: Information gets from this study show us that we couldn't guess bacterial sensitivity against antibiotics. Conclusion: Treatment must be done based on antibiogram results. It is better to find some other useful techniques that results soon be received by physicians.